The Relationship between Religion and Ethics in Quran - Abdulhussein Khosropanah (اخلاق وحیانی)
Ethics explains various descriptive and prescriptive areas of epistemological, logical and valuable topics. Defining the relationship between ethics and religion is one of the common topics in ethics researches. In here morals means statements and ethics, and religion a series of realities expressing mundane vision, manner and actions leading to human happiness. There are three approaches in defining the relationship between the ethics and religion: differentiation, unification and interaction. Utilizing Quranic verses, author has expressed the ethics interaction theory and religion independence to ethics and vice versa.